Duration of Steam Distillation Affects Essential Oil Fractions in Immortelle (Helichrysum italicum) - Marinko Petrović; Vesna Petrović; Zdenko Mlinar; Sandra Babić; Jerko Jukić; Tatjana Prebeg; Dario Kremer (Horticulturae, 2024)
The composition of the essential oil depends on the duration and conditions under which the distillation of the plant material is carried out. In this study, one sample without fractionation and eight fractions (each after 15 min of steam distillation) of the essential oil of cultivated H. italicum were analysed by gas chromatography-mass spectrometry (GC-MS). The steam conditions for all samples were as follows: flow rate 800 L/h, temperature 104 °C, and pressure 0.4 bar. The test of the antimicrobial activity was performed with the modified Kirby–Bauer method (disc diffusion method) on non-selective nutrient media (blood agar) using the reference bacterial and fungal strains. A total of 75 different components were found in the essential oil samples obtained. A shorter distillation time makes the oil richer in monoterpenes and more suitable for the perfume and cosmetics industry. On the other hand, prolonged distillation leads to the essential oil being enriched with sesquiterpene oxides, which can have a negative effect on the fragrance of the essential oil. The essential oil of H. italicum showed antimicrobial activity only against Staphylococcus aureus ATCC 25923, and the best activity was shown by the sixth fraction.